The Sizes and Types of Cities - J.V. Henderson (Queen's University, Department of Economics, 1972)
This paper presents a simple general equilibrium model of an economy where production and consumption occur in cities. The paper focuses on the different sizes and types of cities generated by market forces and whether these market forces generate optimally size cities. Before the model is presented, four complex questions are naively answered, revealing the most basic concepts underlying the paper and intellectual debts to the existing literature. First the model of a single city is presented. How factor rewards and cost of living vary with city size is analysed. Given these results, the paper presents an analysis of market equilibrium and optimum city size. Finally, equilibrium in an economy with multiple types of cities is examined. At the end of the paper, we discuss how natural resources and transportation costs in trade can be integrated into the model. Throughout the paper, it is assumed that capital and labour are scarce resources and perfectly mobile within the economy. The economy is situated on a flat featureless plain, large enough so that land per se is never a scarce resource (although location will be a scarce resource). This non-critical assumption implies the opportunity cost of land is zero. Lastly, there are no specified transport costs of inter-city trade.
Keywords: 330